A novel NTC ceramic based on La2Zr2O7 for high-temperature thermistor. Issue 5 (May 2022) - Chen, Xiaoyi; Li, Xiaohui; Gao, Bo; Kong, Wenwen; Zhao, Pengjun; Chang, Aimin
Abstract: A novel negative temperature coefficient material based on lanthanum zirconate ceramics was proposed for high-temperature applications. This material was synthesized through a solid-state reaction by sintering at 1923 K for 10 h in air. The X-ray diffraction and scanning electron microscopy results confirmed that La2 Zr2 O7 ceramics exhibited a pyrochlore phase with a relative density of 98.2 %. The resistance–temperature characteristics of the material revealed that La2 Zr2 O7 ceramics exhibited an NTC feature within the broad temperature range of 973–1773 K in addition to maintaining high thermal constant B, and resistivity to ensure good sensitivity at high temperatures. These properties, along with high ceiling temperature, unique oxygen insensitivity, and excellent ageing coefficient of <0.7 % at 1773 K, render La2 Zr2 O7 ceramics a promising candidate as thermistor materials with high-temperature NTC.